5e Biënnale Beeldend West-Vlaanderen. - Callens, M.; De Munster, Franck; Defreyne, Gerrit; 5e Biënnale Beeldend West-Vlaanderen, 1996 (Sint-Baafs-Vijve : André Demedtshuis, 1996)
Beaumont, Yves ; Blomme, Greet ; Bouttens, Philippe ; Caen, Francky ; Delrue, Rik ; Demeyere, Dirk ; De Rore, Joel ; Dessauvage, Tjok ; Duyck, Johan M. ; Duyck, Kort ; Godecharle, Jean ; Goethals, Joost ; Hoorne, Emiel ; Jonckheere, Ann-Marie ; Lannoo, Nico ; Raes, Fabien ; Pruvoost, Patrick ; Soenen, Jean Jacques ; Soubry, Bart ; Steel, Christine ; Swimberghe, Gilbert ; Vandeghinste, Lucas ; Verhaeghe, Ria ; Vermoere, Gerda ; Zoete, Dirk
5e Biënnale Beeldend West-Vlaanderen, André Demedtshuis, Sint-Baafs-Vijve, 1996
biografie, bibliografie
Nederlands
boek